A STATE OF ART APPROACH TO THE DESIGN OF COASTAL STRUCTURES UNDER SEISMIC AND TSUNAMI LOADS: PERFORMANCE BASED DESIGN - Ergin, Aysen; Yuksel, Yalcin (YILDIZ TECHNICAL UNIV, 2006)
An evolving design philosophy for port structures in many seismically active regions gained great importance and reflects the observations that: The deformations in ground and foundation soils and the corresponding structural deformation (vertical and horizontal displacement) and stress states are key design parameters. Performance based design, depending on the coastal structure type, is carried out under the design seismic loads and based on the structural performance and the corresponding deformations within the allowed limits. In the conventional limit equilibrium-based methods, performance of the structure and the corresponding structural deformations and stresses are not viewed as design parameters. Conventional seismic design is basically based on providing capacity to resist (overturning and sliding) a design seismic force, but it does not provide information on the performance of structure when the limit of the force-balance is exceeded. Performance-based design is an emerging methodology whose goal is to overcome the limitations present in conventional seismic design. In this approach, coastal structures are designed under the seismic loads given with a certain probability of occurrence, within the maximum allowable limits of structural deformations and stresses considering the local site effects.
Keywords: Coastal structures; performance based design; earthquake; coastal engineering; Engineering